Analysis of Factors Hindering Teachers’ Effectiveness in Secondary Schools in Lagos State, Nigeria: Policy Implications - Inegbedion, Juliet O. (West African Journal of Open and Flexible Learning, 2016)
Students’ learning outcomes and performance are often used in determining the quality of an educational system. The performance of Nigeria secondary school students in the West African Examination Council (WAEC) which is their final examination has been worrisome. As of 2015, students' pass grades has generally not gone beyond 38.68 per cent. It is observed that teachers receive much of the blame for the poor performance. This study therefore tried to find out factors that may be affecting teachers’ effectiveness. One research question was raised to find out the extent to which the effectiveness of teachers is hindered by factors affecting their effectiveness, also one hypothesis was raised to test if there was any significant difference in teachers’ consideration of determinants for effectiveness in public secondary schools based on their educational background. To achieve this, 322 teachers were sampled from Lagos State public secondary schools. A questionnaire was structured and administered. The study found a lack of interest for the job, poor interpersonal relationship, an unconducive learning environment, personal stress and workload, influx of new learning and information technology as factors that hinder teachers’ effectiveness. Review of policies and implementation procedures was recommended to enhance teachers’ effectiveness.
Keywords: Quality education; Teachers’ characteristics; Teachers’ effectiveness